Evaluation of an Aboriginal and Torres Strait Islander strengths based coaching program: a study protocol - Alison Brown; Fiona Mensah; Graham Gee; Yin Paradies; Samantha French; Lea Waters; Kerry Arabena; Gregory Armstrong; Jan Nicholson; Stephanie J. Brown; Kelsey Hegarty; Rebecca Ritte; et al. (BMC, 2021)
Abstract Background Increasingly, strength-based approaches to health and wellbeing interventions with Aboriginal and Torres Strait Islander Australians are being explored. This is a welcome counter to deficit-based initiatives which can represent a non-Indigenous view of outcomes of interest. However, the evidence base is not well developed. This paper presents the protocol for evaluating a strengths-based initiative which provides life coaching services to Aboriginal and Torres Strait Islander community housing tenants. The study aims to evaluate the effect of life coaching on social and emotional wellbeing (SEWB) of tenants in three Victorian regions. Methods The More Than a Landlord (MTAL) study is a prospective cohort study of Aboriginal Housing Victoria tenants aged 16 years and over that embeds the evaluation of a life coaching program. All tenant holders in one metropolitan and two regional areas of Victoria are invited to participate in a survey of SEWB, containing items consistent with key categories of SEWB as understood and defined by Aboriginal and Torres Strait Islander peoples, and key demographics, administered by Aboriginal and Torres Strait Islander peer researchers at baseline, 6 and 18 months. Survey participants are then invited to participate in strengths based life coaching, using the GROW model, for a duration of up to 18 months. Indigenous life coaches provide tenants with structured support in identifying and making progress towards their goals and aspirations, rather than needs. The study aims to recruit a minimum of 200 survey participants of which it is anticipated that approximately 73% will agree to life coaching. Discussion The MTAL study is a response to Aboriginal and Torres Strait Islander community and organisational requests to build the evidence base for an initiative originally developed and piloted within an Aboriginal controlled organisation. The study design aligns with key principles for research in Indigenous communities in promoting control, decision making and capacity building. The MTAL study will provide essential evidence to evaluate the effectiveness of strengths-based initiatives in promoting SEWB in these communities and provide new evidence about the relationship between strengths, resilience, self-determination and wellbeing outcomes. Trial registration This trial was retrospectively registered with the ISRCTN Register on the 12/7/21 with the study ID: ISRCTN33665735 .